2013
DOI: 10.1177/1479164113479618
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble receptor for advanced glycation end products (sRAGE) is independently associated with cigarette smoking in non-diabetic healthy subjects

Abstract: The receptor for advanced glycation end products (RAGE) is a cell surface receptor of immunoglobulin superfamily and is highly expressed in the lung tissue. 1 The lung tissue is directly exposed to cigarette smoke in smokers, and the cigarette smoke has been shown to elevate RAGE expression in cultured cells and in the lung tissues of animals. 2 Some of the diseases prevalent among cigarette smokers, particularly atherosclerotic cardiovascular diseases and cancer, have also been shown to be linked with RAGE si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 5 publications
2
36
0
Order By: Relevance
“…The present study is based on the hypothesis that periodontal inflammatory conditions are worse among smokers with T2DM than never‐smokers with T2DM. This was mainly speculated because both hyperglycemia and habitual smoking enhance the formation and accumulation of AGEs in the periodontal tissues, which jeopardize periodontal health 9,16 . Interestingly, in the present study, clinical and radiologic parameters of periodontal inflammation (PI, BOP, PD ≥4 mm, AL, and MBL) were comparable among smokers and never‐smokers with T2DM.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The present study is based on the hypothesis that periodontal inflammatory conditions are worse among smokers with T2DM than never‐smokers with T2DM. This was mainly speculated because both hyperglycemia and habitual smoking enhance the formation and accumulation of AGEs in the periodontal tissues, which jeopardize periodontal health 9,16 . Interestingly, in the present study, clinical and radiologic parameters of periodontal inflammation (PI, BOP, PD ≥4 mm, AL, and MBL) were comparable among smokers and never‐smokers with T2DM.…”
Section: Discussionmentioning
confidence: 46%
“…The deleterious effects of tobacco smoking on oral and systemic health are well documented 11‐15 . Habitual tobacco smoking has also been associated with an increased expression of receptors of AGEs in the gingival tissues 16 . This in turn jeopardizes the chemotactic and phagocytic functions of polymorphonuclear leukocytes and provokes a pro‐inflammatory effect by stimulating the secretion of cytokines and reactive oxygen species that directly cause breakdown of periodontal tissues 17‐20 .…”
mentioning
confidence: 99%
“…Previous studies 18‐20 have also confirmed that CSs exhibit significantly greater number of sites with plaque accumulation, clinical AL, and PD ≥4 mm compared with NSs. One explanation in this context is that tobacco smoking is associated with increased expression of AGEs and their receptors in gingival tissues, which exacerbate oxidative stress and inflammatory responses 21 . BOP (a classic marker of periodontal disease severity 22 ) was masked among individuals in groups 1 and 2 compared with those in group 3.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] Among these various factors, age, RAGE polymorphisms, smoking body-mass index and ethnicity could well play an important role in varying sRAGE levels. [49][50][51][52] Furthermore, strong evidence suggests a role of kidney dysfunction in increased sRAGE levels, although the specific mechanisms are unclear. 19,20,53 Compared to healthy young individuals, significantly higher sRAGE levels have been reported in healthy centenarians, 54 and a difference of around 500 pg/mL sRAGE has been associated with Gly82Ser polymorphism.…”
Section: Discussionmentioning
confidence: 99%